Xylanase gene from a locally isolated bacterium - Hussain, M.H.; Chong, N.F.M.; Chan, C.S.W.; Safarina, A.; Husaini, A. (Penerbit Universiti Kebangsaan Malaysia, 2011)
A xylanolytic bacterium was isolated from sago plantation humus. Results from the morphological observation, biochemical tests and 16s rRNA sequencing suggested the bacterium to be Klebsiella pneumoniae. Due to the xylanolytic activity of this bacterium, isolation and characterization of the xylanase gene were attempted. A distinct fragment of about 650 bp was successfully amplified using PCR and cloned into Escherichia coli XL-1 Blue. A BLAST search confirmed that the DNA sequence from the amplified fragment was endo-1,4-beta-xylanase gene from the family 11 glycoside hydrolase. It showed 98% homology with Bacillus subtilis xylanase gene. In silico characterisation showed an open reading frame encoding a 213 amino acid sequence with a molecular weight of 23.3 kDa and theoretical isolectric point (pI) at pH 9.42.